1984
DOI: 10.1111/j.1699-0463.1984.tb04396.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise and Fasting on the Myocardial Protein and Lipid Metabolism in Experimental Bacterial Myocarditis

Abstract: A generally nonlethal Salmonella typhimurium infection in weanling rats produced bacterial myocarditis and myocardial hyperplasia. Myocardial lesions were characterized by focal infiltrates of inflammatory cells (predominantly mononuclear). segmental myocyte necrosis, and incipient fibrosis. Although bacterial infections are infrequently associated with myocarditis, the S. typhimurium infection in young rats produced a new experimental model of diffuse myocardial inflammatory foci. Biochemical changes in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…To examine this, we used voluntary unloaded wheel running, an established model of physiologic cardiac hypertrophy, [23][24][25] to determine whether cardiac Atg could be induced as it is in other muscles in response to exercise. [26][27][28] We found that hearts from CHIPÀ/À mice respond to voluntary exercise with an enhanced autophagic response that is associated with an exaggerated hypertrophic phenotype. We further determined that CHIP plays a role in regulating Akt signalling in cardiomyocytes.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…To examine this, we used voluntary unloaded wheel running, an established model of physiologic cardiac hypertrophy, [23][24][25] to determine whether cardiac Atg could be induced as it is in other muscles in response to exercise. [26][27][28] We found that hearts from CHIPÀ/À mice respond to voluntary exercise with an enhanced autophagic response that is associated with an exaggerated hypertrophic phenotype. We further determined that CHIP plays a role in regulating Akt signalling in cardiomyocytes.…”
Section: Introductionmentioning
confidence: 82%
“…It is already well documented that the ubiquitin ligase CHIP plays a critical role in maintaining cardiac structure and function during times of stress, prompting us to examine whether CHIP is involved in autophagic protein degradation in the heart. To examine this, we used voluntary unloaded wheel running, an established model of physiologic cardiac hypertrophy, to determine whether cardiac Atg could be induced as it is in other muscles in response to exercise . We found that hearts from CHIP−/− mice respond to voluntary exercise with an enhanced autophagic response that is associated with an exaggerated hypertrophic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Impairment in both formation and downstream lysosomal degradation of autophagosomes triggers mitochondrial and lysosomal pro‐apoptotic pathways, and therefore culminates in cardiomyocyte death 15,17. There is increasing evidence showing that exercise activates autophagy in muscle 1921. Resistance exercise causes a significant increase in protein degradation activities, such as lysosomal hydrolyase and Vps34,19,20 and increases the content of myocardial protein synthesis,20,21 thus stimulating protein turnover.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence to show that exercise up‐regulates autophagy, and increases the protein turnover rate;1921 however, it is unknown whether exercise has the same effect on the failing heart. In the present study, we investigated the effect of exercise training on cardiac function in an infarcted rabbit model explored the possible mechanisms of this effect, by analysing biomarkers of oxidative stress, antioxidant capacity, autophagy, apoptosis, and fatty acid utilization.…”
Section: Introductionmentioning
confidence: 99%
“…In several infections the accumulation of fat occurs in infected tissues, often accompanied by tissue necrosis: when arteries are the targets of the microorganisms, arteriosclerotic changes may ensue (Ilback et al, 1984c;Ilback et al, 1990;Nystrom-Rosander et al, 2003). Inflammatory fluid seems to accelerate the uptake of lipoproteins in resident macrophages (Raymond et al, 1985) and the increased uptake of lipids in the heart in coxsackievirus myocarditis is histologically localized to "macrophage dense" areas (Ilback et al, 1990).…”
Section: Tissue Distribution Of Nutrients and Xenobiotics In Infectionmentioning
confidence: 96%